Designed and Implementing of Quadcopter Control Unit Capable of Tracking and Detecting Airplanes Types - Aslinezhad, Mehdi; Hosseinzadeh, Massoud; Heidari, Farsad (International Journal of Engineering and Technology, 2020)
The goal of this study is to design and implement a new idea for air-launched quadcopter control unit using the digital video processing. In this study, it’s endeavored to transmit the captured videos by a camera embedded on the quadcopter via video transceiver and after pro-cessing, the ground station relays appropriate command to the quadcopter to tracking target. Moreover, it’s desired to detect a target in the sky and both stay in one direction until detect the target when intercepting toward the target and the quadcopter intercepts the target in every direction. In order to identify the type of aerial targets, the dimensions are studied at different intervals, which makes military and non - military goals detected at different intervals.